International Monetary Fund Annual Report 1987. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1987)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1987. The report highlights that the international economic and financial situation changed substantially during 1986 and the early part of 1987. Economic growth in the industrial countries slowed, real primary commodity prices continued to decline, external imbalances widened despite ongoing adjustments in real trade balances, protectionist pressures and actions intensified, and the external financial situation of many developing countries deteriorated further.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet